Total Diplomacy, Total History: Military Historians and the Indonesian Peace Corps - Kusuma; Sarkawi B. Husain (istory Department, Faculty of Social Sciences, Universitas Negeri Semarang in collaboration with Masyarakat Sejarawan Indonesia (Indonesian Historical Society), 2025)
Abstract: This research explores the concepts of Total Diplomacy and Total History, focusing on the role of military historians in the Indonesian peacekeeping force. The Indonesian government employs military diplomacy by deploying Garuda Contingent troops on global peace missions, aligning with the constitutional mandate of the Republic of Indonesia. As part of Indonesia’s total diplomacy strategy, military diplomacy is analyzed by deploying peacekeeping troops, engaging with other diplomatic instruments, and involving military historians to document missions comprehensively. The discussion encompasses the definition of military diplomacy, its international role, and its impact on Indonesia's global image. Military historians face challenges, including disrupted historical record-keeping and changes in the composition of historical officer positions. To overcome the obstacles in writing military history, the concept of Total History becomes relevant, integrating various scientific disciplines to support the historiographic process. In peacekeeping operations, military historians must grasp the totality of this scientific approach and present it more engagingly, meaningfully, and solution-oriented, relevant to the conflict areas they oversee. Abstrak: Penelitian ini mengkaji konsep Total Diplomacy dan Total History dengan menyoroti peran sejarawan militer dalam misi pasukan perdamaian Indonesia. Pemerintah Indonesia menjalankan diplomasi militer melalui pengiriman pasukan Kontingen Garuda dalam misi perdamaian dunia, sebagai bentuk pelaksanaan amanat konstitusi Republik Indonesia. Dalam kerangka strategi total diplomacy, diplomasi militer dianalisis melalui perannya dalam mengerahkan pasukan perdamaian, berinteraksi dengan instrumen diplomatik lainnya, serta melibatkan sejarawan militer untuk mendokumentasikan misi secara menyeluruh. Pembahasan mencakup definisi diplomasi militer, perannya di kancah internasional, dan dampaknya terhadap citra global Indonesia. Sejarawan militer menghadapi berbagai tantangan, seperti terputusnya pencatatan sejarah dan berubahnya struktur penempatan personel sejarah. Untuk mengatasi kendala dalam penulisan sejarah militer, konsep Total History menjadi penting, karena mengintegrasikan berbagai disiplin ilmu guna mendukung proses historiografi. Dalam operasi perdamaian, sejarawan militer dituntut untuk memahami pendekatan ilmiah secara menyeluruh dan menyajikannya secara lebih menarik, bermakna, serta berorientasi pada solusi, terutama dalam konteks wilayah konflik yang mereka pantau.